Juridical Study in Implementing A System on Licensing for Establishing Buildings in Banjarmasin City - Aufa, Muhammad Fikri; Syahbania, Noor; Pradana, Fiko Agung (Universitas Muhammadiyah Yogyakarta, 2022)
A building permit is a permit granted by a regional head to a building owner to construct a new structure, expand an existing structure, maintain existing facilities, and reduce the size of existing structures while adhering to all applicable technical and administrative standards. The requirements to apply a building permit had been governed in Article 7 of Banjarmasin City Regulation Number 15 of 2012 concerning Building Permits. The Investment and Integrated One-Stop Services Agency/DPMPTSP Banjarmasin City was the subject of this study. The research aimed to discover and examine the mechanisms for issuing a building permit and the roadblocks during the application process. This study employed empirical juridical research methods. The data gathered were then analyzed using descriptive qualitative methods, i.e., describing and interpreting data about societal conditions, attitudes, viewpoints, disputes between two or more situations, factual differences, and their impact on a position. The development of a planned and systematic method of granting building licenses in Banjarmasin had gone smoothly. However, there were impediments to the procedure and its implementation, making the process of granting building licenses difficult.